Matlab/Simulink model of solar PV array with perturb and observe MPPT for maximising PV array efficiency - Ibrahim, O. (Institute of Electrical and Electronics Engineers Inc., 2015)
The efficiency of commercially available solar PV module is very low in the range of 10-25 In order to maximise their operating efficiency and to reduce installation cost, maximum power point trackers (MPPT) are coupled with the system. The output power of solar PV depends on solar irradiance level, incident angle, temperature and load current which all contribute to non-linear varying I-V characteristic during operation. MPPT ensures that a PV cell, module or panel is operated and maintained at the reference voltage that correspond to maximum power point for particular operating solar irradiance and cell temperature. A 220 W solar PV panel is modelled in Matlab-Simulink to study solar PV characteristics under different solar irradiance and working cell temperature. A Perturb & Observation MPPT technique incorporated for maximising the output power of the PV panel shows that the percentage deviation from the ideal PV power is about 10 for different operating solar irradiance and cell temperature. Â© 2015 IEEE.